Heat transfer during reflux condensation of R134a inside a micro-fin tube with different tube inclinations - Yildiz, S.; Duymaz, G.; Ziegler, F.; Auracher, H. (ELSEVIER SCI LTD, 2017)
This study presents an experimental investigation of the heat transfer occurring during reflux condensation of refrigerant R134a in an inclined micro-fin tube (0.008 m OD, 0.5 m length). The experiments were carried out at a system pressure of 0.74 MPa and at inclination angles of 30, 38, 45, 60 and 90 from the horizontal. The experiments indicated that the inclination angle has a significant effect on heat transfer during reflux condensation. The maximum reflux heat transfer coefficient was found at 30 inclination angle. At this arrangement, the heat transfer increased by a factor of 2.45 compared to the vertical case. A comparison with previous studies suggests that the heat transfer in a micro-fin tube is 2.2 times better than that in a plain tube, and 1.34 times better than that in a plain rectangular channel both at 30 inclination. (C) 2016 Elsevier Ltd and IIR. All rights reserved.
Keywords: Reflux condensation; R134a; Heat transfer; Micro-fin tube; Inclined tube; PRESSURE-DROP; FLOW; REFRIGERANTS; R-134A; Thermodynamics; Engineering